MUTU SENSORI SUSU FERMENTASI PROBIOTIK SELAMA PROSES FERMENTASI MENGGUNAKAN Lactobacillus casei subsp. casei R-68 - Azli Ananta Ginting; Usman Pato; Vonny Setiaries Johan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Probiotic fermented milk by Lactobacillus caseisubsp. casei R-68 with skim milk as a raw material expected to produce probiotik fermented milk with more complete nutriotional value and health benefits. The purpose of this study was to determine the best fermentation on the quality of fermented milk. This study used a Completely Randomized Design with six treatmentsnamely P1 = fermentation time 6 hours, P2 = fermentation time 9 hours, P3 = fermentation time 12 hours, P4 = fermentation time 15 hours, P5 = fermentation time 18 hours,P6 = fermentation time 21 hours and three replications. Data were analyzed using ANOVA, followed by DNMRT at 5% level. The results show that the fermentation time significantly (P <0.05) influencedthe sensory test by descriptive and hedonic on taste and viscosity, but did not significantly affect (P> 0.05) the moisture, fat, ash contentsas well asthe sensory test by descriptive and hedonic on color and the sensory test by descriptive on viscosity. It was concluded that the best quality of fermented milk was P4 (fermentation time 15 hours). Keywords:Skimmed milk, fermentation time, Lactobacillus caseisubsp.casei R-68, fermented milk.MahasiswaFakultasPertanian, Universitas RiauDosenFakultasPertanian, Universitas RiauJOM Faperta Vol. 3 No. 1 Februari 2016 MahasiswaFakultasPertanian, Universitas RiauDosenFakultasPertanian, Universitas RiauJOM Faperta Vol. 3 No. 1 Februari 2016